Cementless metaphyseal reverse shoulder arthroplasty: our preliminary experience - Micheloni, Gian Mario; Salmaso, Gianpaolo; Berti, Mattia; Bortolato, Sara; Zecchinato, Gino; Momoli, Alberto; Giaretta, Stefano (Acta Biomedica Atenei Parmensis, 2019)
Reverse shoulder arthroplasty (rTSA) is a largely used procedure with a wide variety of indications. The incidence of this surgery is increased in recent years and the literature expects similar trend for them future. Metaphyseal stem rTSA seems to be a promising solution considering major objectives the preservation of humeral bone stock and ease of revision. In our study we analyzed 19 patients treated with cementless metaphyseal stem rTSA for osteoarthritis (group A) and acute fractures (group B). In group A (7 patients) the average Constant score improved from 21,57 (16-29) to 56,85 (38-72), the average SST improved from 2,29 (1-4) to 9,43 (8-12) and the mean VAS score improved from 14,29 to 4,86. In group B (12 patients) the mean Constant-Murlay score at last follow up was 42,17; the average SST was 7 and average pain score was 8,92. Overall active range-of-motion (ROM) improved significantly. Surgical considerations, clinical (analyzing Constant score and Simple Shoulder Test) and radiological short-term outcomes are encouraging, with low rate of complications. Long term follow-up studies are necessary to confirm our findings and the potential benefits related to these implants.